Dukungan Sosial Dari Orang Tua Asuh Kepada Anak Berhadapan Dengan Hukum Dalam Proses Rehabilitasi Sosial - Hidayat, Muhamad Rizky; Annisah, Annisah; Sekar, Dwi Amalia Chandra (UI Scholars Hub, 2024)
The social rehabilitation process in which children face legal conflict is not easy, especially when they are far from their families. This article aims to examine the forms and benefits of social support from foster parents to Children in Conflict with the Law (ABH) who are undergoing the process of social rehabilitation. Descriptive qualitative research was conducted at the Social Rehabilitation Center for Children who Need Special Protection (BRSAMPK). This research was conducted in March-July 2021. Data collection was carried out through in-depth interviews with 13 informants, consisting of children in conflict with the law, heads of social services and rehabilitation, foster parents, and social workers. The results of the research show that foster parents BRSAMPK Handayani Jakarta provide social supports to children: emotional support in the form of giving affection, appreciation support in the form of giving positive sentences, instrumental support in the form of giving rewards, and informative support in the form of input and suggestions. The social support provided by foster parents can fill the absence of the family and help the child undergo the social rehabilitation process. The social support received by ABH makes them feel comfortable and open with their foster parents; the social rehabilitation process is smoother; and encourages changes in ABH behavior. The conclusion is that the social support provided by foster parents who are significant others has a very crucial role in the social rehabilitation process and fulfillment of ABH's rights. This article contributes to the study of social welfare by providing a more in-depth description of the role of social support for ABH in social rehabilitation process, facilitating behavioral change, and fulfilling the rights of ABH.